Iowa Birdline update, July 30, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for July 30, 1990. Highlights of the update include sightings of a white immature Little Blue Heron, a Ringed Turtle-Dove, nesting House Finches, and a fourth report of a Red Crossbill. Also of note were several observations of shorebirds, including a Wilson's Phalarope, a Short-billed Dowitcher, Stilt Sandpipers, and numerous American White Pelicans. Epson - sheet feed/flatbed